Another development challenge: gaining emancipation from a functional hegemony in accounting and management control research. Issue 1 (5th November 2020) - Alam, Saiful; Ranasinghe, Seuwandhi B.; Wickramasinghe, Danture
Abstract : Purpose: The purpose of this paper is to reflectively narrate the methodological journey of the authors in penetrating the positivitic hegemony of accounting and management control research in their native countries, Bangladesh and Sri Lanka. Design/methodology/approach: This paper offers an auto-ethnography to demonstrate the lack of diversity in accounting, accountability and management control research. Findings: Global developments in accounting and accountability reforms entail not only about how developing countries being governed through these reforms but also about how accounting research itself can be pursued alternatively. In the past several decades, a camp of British accounting researchers initiated a programme of research in this direction. Inspired by post-positivistic traditions, they aimed to explore how these reforms are predicated upon cultural-political milieus in developing countries. However, the academia in most accounting and management researchers from local universities in these countries are blindly bombarded with positivistic traditions. Originality/value: The authors unpack how this hegemony formed and how attempts were made towards some emancipatory potentials.